2020
DOI: 10.1088/1757-899x/934/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low cost lasers for graphene oxide thin films reduction

Abstract: In this work we made reduction of graphene oxide films with different low-cost lasers (near IR (1060 nm) and blue (445 nm) to investigate possibility of such films usage for flexible electronic and nanoelectronic applications. We successfully showed possibility of graphene oxide reduction with both types of laser but blue laser showed better uniformity of reduced graphene oxide film parameters including film morphology, resistance and Raman intensity ratios. We showed that reduction with near IR laser spills o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Their work demonstrated higher power densities correlated to lower sheet resistance films, achieving values as low as 1300 Ωsq −1 using a CO 2 laser. Komarov et al [ 40 ] compared reduced graphene oxide films produced using low-cost lasers, concluding that shorter wavelengths produce better quality films. Mortazavi et al [ 41 ] also demonstrated the advantages of a shorter wavelength using a 10 ns pulsed KrF excimer laser operating at a wavelength of 248 nm to thermally reduce graphene oxide, achieving the greatest reduction at laser fluences of 10 mJcm −2 to 30 mJcm −2 before the onset of ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Their work demonstrated higher power densities correlated to lower sheet resistance films, achieving values as low as 1300 Ωsq −1 using a CO 2 laser. Komarov et al [ 40 ] compared reduced graphene oxide films produced using low-cost lasers, concluding that shorter wavelengths produce better quality films. Mortazavi et al [ 41 ] also demonstrated the advantages of a shorter wavelength using a 10 ns pulsed KrF excimer laser operating at a wavelength of 248 nm to thermally reduce graphene oxide, achieving the greatest reduction at laser fluences of 10 mJcm −2 to 30 mJcm −2 before the onset of ablation.…”
Section: Introductionmentioning
confidence: 99%